The EU Factor as a Determinant of Inflows of Foreign Direct Investment to Poland, Czech Republic and Hungary - Pilarska, Czesława; Wałęga, Grzegorz (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2016)
The article examines issues related to the inflow of foreign direct investment (FDI) to three countries that acceded to the European Union in the last decade, Poland, Czech and Hungary. These countries were chosen because they are considered transformational leaders of change, and also because, since the opening of their economies to the inflow of foreign capital, they have attracted the largest amount of direct investment among all the members from the region of Central and Eastern Europe. In this article we examine the extent to which the flow of FDI to Poland, Czech and Hungary was a result of the impact of traditional factors such as market size, labour costs or the openness of the economy, and in so far as it was based on a factor known as the “EU factor”. Empirical studies, based on data for the period 1996–2012, indicate that the signing of an association agreement with the EU has brought considerable transformational benefits to the countries in terms of FDI inflows. The impact of full membership in the European Union on the ability of countries to attract inward FDI stock is also assessed.